A Partial Defense of the Non-Commercialization of Surrogacy - Fulfer, Katy (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
Canada’s Assisted Human Reproduction Act justifies its non-commercialization approach to surrogacy on the grounds that commercial payments for surrogacy commodify women and are exploitative. However, empirical evidence suggests that payments in surrogacy are not exploitative, at least not to an extent that would warrant criminalizing payments. Given skepticism about the connection between exploitation and commodification, I explore whether commodification critiques can ground an alternative justification for the non-commercialization of surrogacy. First, I examine Vida Panitch’s argument that commodification critiques are flawed for being absolutist, that is, they cannot identify what makes some surrogacy transactions better or worse than others. Second, I examine Anne Phillips’ rearticulation of a commodification critique: Commercial surrogacy is problematic because it undermines equality in a democratic society. I argue that Phillips’ revision can escape absolutism and provide a better justification for Canada’s non-commercialization stance. However, it also entails that the preference for criminalizing payments is weakened, as other policy solutions might be effectively implemented to protect equality. As a result, I propose a shift in how commodification is appealed to: Less attention should be paid to abstract values and more attention should be given to how those values are enacted relationally between members of a political community. I also tentatively suggest that commodification critiques might provide a normative basis in Canadian policy for a self-sufficiency regulatory framework, which centres on values such as solidarity and the public good.